2020
DOI: 10.18231/2456-9267.2018.0017
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological spectrum of dermatological lesions – An experience at tertiary care centre

Abstract: Introduction: Skin is the largest sensory organ of the body and acts as a barrier against various harmful environmental agents. Thus it is involved in wide spectrum of disorders ranging from inflammatory conditions to neoplastic lesions. Skin biopsy followed by histopathological study is needed for accurate diagnosis, identifying etiological agent with special stains wherever feasible, and to help clinicians to decide the appropriate management. But for instance, only few statistical studies have been carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
2
0
0
Order By: Relevance
“…A similar study conducted by Mamatha et al 15 18 in 2010 reported 76.8% cases having positive correlation and 23.2% with absent correlation. This is in confirmation with our study.…”
Section: Resultssupporting
confidence: 50%
“…A similar study conducted by Mamatha et al 15 18 in 2010 reported 76.8% cases having positive correlation and 23.2% with absent correlation. This is in confirmation with our study.…”
Section: Resultssupporting
confidence: 50%
“…The age range of the patients in this study was between the first and eighth decades, which is similar to the findings of Ayesha et al [11], Mehar et al [12], Yalla et al [13], George et al, [14], Deepthi et al [15], Gaikwad et al [16], Bharadwaj et al [17], Sushma et al [18], and Gupta et al [19]. Patients in studies by Mamatha et al [20], Singh et al [21], Agrawal et al [22], Narang et al [23], and Kafle et al [24] ranged in age from the first to the seventh decade, while patients in studies by Gulia et al [25] ranged in age from the first to the ninth decade.…”
Section: Discussionsupporting
confidence: 89%